Wrap Yourself a Chunk of Cheese Business - Dow Chemical Company
Color print advertisement for Durafilm, transparent packaging manufactured and sold by the Dobeckmun Company, a division of the Dow Chemical Company based in Cleveland, Ohio. The advertisement features stacked blocks of cheese packaged in Durafilm, with accompanying text detailing the packaging's durability and clarify, as well as its ability to seal in flavor and seal out moisture. Dobeckmun (short for Dolan, Becker and Munson, the company's the co-founders) was a leading manufacturer of cellophane bags and cigar pouches. The Dow Chemical Company acquired Dobeckmun in 1957.
Keywords: Dow Chemical Company; Advertising; Advertising, Industrial; Chemical industry; Corporations; Food--Packaging; Packaging; Plastics in packaging